Time and Soul : From Aristotle to St. Augustine. - Zachhuber, Johannes. (Chronoi Series, 2022)
Chronoi: Time, Time Awareness, Time Management　is a book series that presents the work of the Einstein Center Chronoi. The center is dedicated to the investigation of time and time-related subjects such as time awareness, time management, time perception, and temporality from interdisciplinary and transdisciplinary perspectives.